PENGARUH PENAMBAHAN LIMBAH BAN BEKAS TERHADAP KEKUATAN BETON - Handika Setya Wijaya; Evangelino Da Cruz Evangelino (Jurnal Qua Teknika, 2021)
In the world of construction, concrete still plays an important role as the main material used. This is because concrete has several advantages such as ease of work, the use of solid waste as material substitution in the industry is not new. However, the use of solid waste as a substitute for aggregates in concrete has been increasing in recent years, as a promising solution to reduce inorganic solid waste. From the tests carried out in the university tribhuwana to laboratories, it shows that for compressive strength and tensile strength, it decreases. The concrete compressive strength test results with added material in the form of tire chips and in the testing of compressive strength for 5% used tire waste burned 13.22 MPa, as well as 10%, the value burned 9.74 MPa, and for compressive strength test 15% of the value decreases for compressive strength with a mixture of burnt tire chips 4.77Mpa. The graph of the concrete tensile strength test with added material is in the form of tire chips and in testing the tensile strength for used tire waste 5% with for concrete that is not burned 1.844Mpa value. Likewise with 10% for unburned concrete the value of 2,020Mpa with a mixture of used tire waste as added material. And for the tensile strength test 15% the value decreases for non-burned concrete with a quality of 1.544Mpa.